The Influence of the English Translation Methods on High School Students’ Comprehension of Clips and Films - Villanueva, Patrick V.; Tolentino, Jozelle; Ferraris, Evelyn; Navotas, Rose (International Journal of Psychosocial Rehabilitation, 2020)
Globalization in the 21st century allows faster communication than we’ve ever had. This allows foreign content such as films and entertainment to come even though they are rarely being translated to the spoken language if the country it is being aired to. Cable channels like Home Box Office (HBO) and Movie Central do not usually construe their movies which leads to confusion for some audiences. Globalization affected Filipinos in forms of entertainment as they watch not only American movies but also Anime and Asian dramas.